1996
DOI: 10.1002/(sici)1096-9101(1996)19:4<424::aid-lsm7>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous‐wave laser systems on stapes footplate

Abstract: Background und Objective: The aim of the present study was to clarify which of the presently available continuous-wave laser systems are best suited for application in stapes surgery. Study DesignlMuterhZs and Methods: Isolated human stapes and bovine compact-bone platelets were used to investigate the connections between the parameters of various laser systems and their effects on bone tissue. The purpose was to optimize the laser parameters required to achieve a perforation measuring 500 pm to 600 pm in diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…During vaporization of connective tissue in the oval niche or direct irradiation of the prosthesis, heat may be conducted to the vestibulum if the piston is still in the stapedotomy opening. However, in previous studies, we and others have experimentally determined and demonstrated safe parameters for the CO 2 laser application in animals and humans …”
Section: Introductionmentioning
confidence: 98%
“…During vaporization of connective tissue in the oval niche or direct irradiation of the prosthesis, heat may be conducted to the vestibulum if the piston is still in the stapedotomy opening. However, in previous studies, we and others have experimentally determined and demonstrated safe parameters for the CO 2 laser application in animals and humans …”
Section: Introductionmentioning
confidence: 98%
“…13 The total energy minimization required to prevent inner ear damage is best achieved by the single application of a focussed laser beam. [12][13][14] The laser industry (Lumenis Co., Tel Aviv, Israel) cooperated in the development of microprocessor-controlled scanner systems that move the focussed laser beam over a defined and selectable area in short time intervals with the aid of rotating mirrors. These systems are the first to achieve a perforation large enough for a piston by applying the laser a few times or only once.…”
mentioning
confidence: 99%
“…So fanden Wong et al [23] bei einer Oberflächenanalyse nach Laserbeschuss durch Argon-, cwCO 2 -, und KTP-Laser deutliche Koagulationseffekte, Schmelzzonen an den Kraterrändern und Risse durch explosive Gaseruptionen. Untersuchungen von Jovanovic et al [9,17,22,24] ganischer Substanzen mit anschlieûender eruptiver Freisetzung organischer und anorganischer Knochensubstanz zuschreibt.…”
Section: Ergebnisseunclassified